PBS kids: Get Up and Dance! - PBS Distribution LLC (Old Saybrook, Connecticut : PBS Distribution LLC, 2023)
Join the dance party with some of your favorite friends from PBS KIDS! Groove with Alma as she helps Eddie and Beckacreate a brand-new mash-up dance. Then Mr. Lion encourages Elinor and her pals to create their own dance routine, while Luna gives Leo a tango lesson, and much, much more! Primary (PreK-2). PBS; 841887048224; 1 Disc(s); 190 min; Childrens; TVY; 07/25/23
[Typographic symbols and accents removed for systems compatibility.]
Widescreen edition.
Rating: TVY.
DVD, color, widescreen, NTSC.
Keywords: Childrens Video; Video recordings